Publisher Correction: JMJD5 is a human arginyl C-3 hydroxylase - Sarah E. Wilkins; Md. Saiful Islam; Joan M. Gannon; Suzana Markolovic; Richard J. Hopkinson; Wei Ge; Christopher J. Schofield; Rasheduzzaman Chowdhury (Nature Communications, 2018)
The originally published version of this Article contained an error in the spelling of the author Md. Saiful Islam, which was incorrectly given as Saiful Islam. This has now been corrected in both the PDF and HTML versions of the Article.